Constitutional Review of ASEAN Charter and Maastricht Treaty: A Comparison of Indonesia and France - Dwi Prastyo, Muhammad Ariff; Cahayarizputra, Albiruwahidhan; Osckardo, Daniel (International Journal of Business, Law, and Education, 2024)
This journal will discuss how the role of constitutional courts in Indonesia and France in reviewing the constitutionality of the ratification law of an international treaty. While both Indonesia and France possess a Constitutional Court/Council, both of them have different principles regarding the constitutional review of international treaties. This paper uses normative research with a descriptive analysis approach. We found that in practice, both Indonesia and France can constitutionally review the ratification of an international treaty. Although the Constitutional Court in Indonesia has never annulled the ratification of an international treaty, there remains the possibility of a treaty being ratified and later revoked by the process of judicial review. Meanwhile in France, while judicial review can conflict with the Constitution, in the case of the Maastricht Treaty this led to constitutional amendments to accommodate Maastricht Treaty with the Constitution instead of annuling the treaty altogether